IMPLEMENTASI KEBIJAKAN PENGAWASAN BARANG IMPOR PADA KANTOR PELAYANAN UTAMA TIPE C SOEKARNO-HATTA - Dwikora Harjo; Jordan Christopher Imanuel (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
The increasing flow of imported goods through air transportation requires customs supervision that is well planned, well coordinated, and responsive to the dynamics of international trade; therefore, the Type C Customs and Excise Main Service Office of Soekarno-Hatta plays a strategic role in ensuring compliance, security, and the protection of national interests. This study aims to analyze the implementation of import goods supervision policies, identify obstacles encountered in their implementation, and examine the efforts undertaken to address these challenges. The research employs a qualitative descriptive method, with data collected through observation, in-depth interviews, and documentation, which were analyzed using data triangulation. The analysis is based on George C. Edwards III’s policy implementation theory, encompassing four key dimensions: communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of import supervision policies has generally been carried out in accordance with applicable regulations; however, several obstacles remain, including limitations in human resources and supporting facilities, high volumes of imported goods accompanied by increasingly complex violation modes, low levels of compliance and understanding among service users, as well as regulatory dynamics and inter-agency coordination complexities. Efforts to address these obstacles include strengthening policy communication and socialization, optimizing the use of information technology and risk management, enhancing the capacity and integrity of officers, and reinforcing coordination and procedural improvements. Overall, the implementation of import goods supervision policies demonstrates a reasonably adequate level of effectiveness but still requires continuous strengthening and adjustment to optimally address future import supervision challenges